Pregnancy in women with Fontan physiology. (December 2011) - Le Gloan, Laurianne; Mercier, Lise-Andrée; Dore, Annie; Marcotte, François; Mongeon, François-Pierre; Ibrahim, Réda; Asgar, Anita; Poirier, Nancy; Khairy, Paul
Advances in the care of patients with a univentricular heart have enabled the majority to survive well into adulthood. Consequently, an increasing number of women with Fontan palliation are contemplating pregnancy. This review summarizes physiologic modifications related to pregnancy in the setting of single-ventricle physiology, discusses potential maternal cardiovascular concerns and describes commonly encountered obstetrical and neonatal complications. Management issues are addressed, including counseling, anesthetic considerations and the need for multidisciplinary specialized care.